Fabrication of CeO2/Fe2O3 composite nanospindles for enhanced visible light driven photocatalysts and supercapacitor electrodes. Issue 29 (7th August 2015) - Arul, N. Sabari; Mangalaraj, D.; Ramachandran, R.; Grace, A. Nirmala; Han, Jeong In
<x xml:space="preserve">Abstract</x> Hybrid CeO2/Fe2O3 composite nanospindles (CNSs) are synthesized by a simple and cost effective co-precipitation method, utilized for wastewater treatment and energy storage applications.